A method to map real-time gamma-ray radiation in urban areas near the soil surface - Pereira, Paulo; Pinto, Luis; Inacio, Miguel; Barcelo, Damia; Brevik, Eric C.; Brevik, Corinne E. (MethodsX, 2025)
Radiation exists naturally in the environment. However, human activities, especially those related to nuclear weapons, energy generation, and medical infrastructures, can increase radioactivity levels in air, soil, and water, threatening human health. Both urban and rural populations can be exposed to radioactivity, making mapping an essential tool for a better understanding of radiation concentration. In this work, we developed a “walk-borne” survey methodology to map real-time gamma radiation (count and dose rate) in an urban area (Vilnius, Lithuania) using a small portable spectrometer (RadiaCode). A detailed method was developed considering 1) RadiaCode test in the field, 2) study site selection, 3) transect design to map count and dose rate, 4) RadiaCode map settings preparation, 5) fieldwork and data preparation, 6) data download and processing, and 7) statistical and spatial analysis. This method will be key to identifying potential radiation sources and accumulation that can be transferable to other environments.•A novel “walk-borne” survey methodology was developed to map real-time gamma-ray radiation using a small portable spectrometer;•High-resolution mapping of potential radiation sources can be identified with their implications for human health•This method can help identify areas with potential radiation risks. [Display omitted]